Comparing hypertonic saline and xylometazoline in allergic rhinitis - Sinha, O. N.; Deswal, Monika (International Journal of Research in Medical Sciences, 2017)
Background: Allergic rhinitis (AR) affects productivity, quality of life and performance at work. Pharmacological agents are widely used and nasal irrigation using hypertonic saline is underused. Methods: All consecutive patients presenting at the outpatient clinic with complaints of AR at Santosh Medical College Hospital from August 1, 2014 to August 31, 2015 were included in the study. Patients were randomly assigned to either xylometazoline nasal drops (0.1%, three times a day, brand Otrivin) or hypertonic seawater saline (2.2%, three times a day, brand Physiomer). They were followed for a period of 2 months. Symptom change was assessed at the start of the treatment and at the end using the Nasal Index Score (NIS), which comprised of grading blocked nose, runny nose, sneezing and eye itching on a 4-point severity scale. Results: 85 patients were included in the final analysis. On the NIS, patients receiving hypertonic nasal drops showed a decrease in mean score by 0.7, 0.5, 0.7 and 0.7 for blocked nose, runny nose, sneezing and eye irritation respectively, all of which were statistically significant. Additionally, more side effects like bloody nasal discharge, respiratory infections and headache were seen with xylometazoline nasal drops. Conclusion: Our findings suggest that using hypertonic nasal drops can reduce the dependence on pharmacological agents like xylometazoline, improve symptoms and quality of life with fewer adverse reactions.